(untitled) (JURNAL PROTEKSI KESEHATAN, 2024)
Healthy food is food that does not contain microbes and chemicals such as dyes and preservatives. Colorants and preservatives are dangerous as food additives such as formaldehyde, borax, rhodamine B, and methanyl yellow. Formalin is an odorless, clear or colorless liquid. Borax is a common harmful cleaner, fungicide, herbicide and pesticide used in everyday life. Rhodamin B and methanil yellow are two examples of illegal food coloring that are commonly used by irresponsible food manufacturers. Methanyl yellow and Rhodamine B are often used as dyes in the textile industry. This study aims to determine the presence of preservatives and coloring agents in takjil food sold in Baru sub-district, Birobuli sub-district, Palu Barat sub-district, and Tondo sub-district, Palu city using a qualitative analysis method with formalin, borax, rhodamin B, and methanil test kits. The results obtained show that all samples sold during the month of Ramadan in the city of Palu do not contain harmful substances and are safe for consumption.